Growth Dynamics: a Comparative Analysis Between Indonesia and the United States - Insyiraah, Haggi; Hutapia, Hutapia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to identify the discriminant factors that distinguish the Gross Domestic Product (GDP) between Indonesia and the United States. Using discriminant analysis method, this study explores the economic variables that contribute to the difference in economic performance of the two countries. The main focus of this analysis is to determine the extent to which variables such as per capita income, exports of goods and services, exports of ICT goods, unemployment with continuing education, manufacturing exports, government spending on education can predict and differentiate the GDP of the two countries. The results showed that there are four significant variables that distinguish the Gross Domestic Product (GDP) between Indonesia and the United States. These variables are national income per capita, export of Information and Communication Technology (ICT) goods, export of manufactured goods, and expenditure on education. Therefore, the government can focus on these variables in order to improve the economy in indonesia.